Urinary steroid profiling in diagnostic evaluation of an unusual adrenal mass. (28th November 2019) - Lenders, N F; Greenfield, J R
Abstract : Summary: Adrenal oncocytomas are rare tumours, with only approximately 160 cases reported in the literature. We report the use of urinary steroid profiling as part of their diagnostic evaluation and prognostication. A 45-year-old woman presented with clinical features of hyperandrogenism. Serum biochemistry confirmed androgen excess and computed tomography (CT) demonstrated a 3.2 cm adrenal tumour with density 39 HU pre-contrast. Urine steroid profiling showed elevated tetrahydro-11 deoxycortisol (THS), which is associated with adrenal malignancy. Laparoscopic adrenalectomy was performed, and histopathology diagnosed adrenal oncocytoma. Serum and urinary biochemistry resolved post-operatively and remained normal at 1-year follow-up. Learning points: Differential diagnosis of adrenal masses is challenging. Current techniques for differentiating between tumour types lack sensitivity and specificity. 24-h urinary steroid profiling is a useful tool for reflecting steroid output from adrenal glands. Gas chromatography-mass spectrometry (GC-MS) of urinary steroid metabolites has sensitivity and specificity of 90% for diagnosing adrenocortical carcinoma. Adrenal oncocytoma are rare tumours. Differentiating between benign and malignant types is difficult. Data guiding prognostication and management are sparse.